Link budgets and system design for positioning systems - Sharp, I.; Yu, K. (Wireless Positioning: Principles and Practice, 2018)
The design of terrestrial radio navigation systems tends to focus on the details of the method of determining the position of a mobile device, based on the properties of the radio signal, and the details of detection and subsequent signal processing. However, the starting point in any design will be in response to a system specification which defines the requirements of each application. These high level requirements are often rather limited in scope, and can vary considerably from application to application. While the widespread adoption of GPS in mobile devices means that the default solution is typically based on applying the capabilities of GPS to a particular application, specific radiolocation applications are such that GPS is not able to meet the requirements; it is these types of applications that are the focus of this chapter. In particular, these will include indoor applications where GPS performs poorly or not at all, applications where there are much higher accuracy requirements than can be achieved by GPS even in outdoor applications, and even security applications where vulnerability to jamming of the signal makes GPS unviable.